Răspunsuri

Cel mai inteligent răspuns!
2014-08-11T23:16:30+03:00

(6-√6)/6√3-(4+3√6)/3√3+(√6-2)/4√3-(3+√6)/2√2=

[(6-√6)/6√3]x√3/√3=    [(6-√6)·√3]/6√3·√3=(6√3-√18)/18=(6√3-3√2)/18=3(2√3-√2)/18=(2√3-√2)/6

[(4+3√6)/3√3]x√3/√3=[ (4+3√6)·√3]/(3√3·√3)=(4√3+3√18)/9=(4√3+9√2)/9

[(√6-2)/4√3]x(√3/√3)=(√18-2√3)/(4√3·√3)=(3√2-2√3)/12

[(3+√6)/2√2]x(√2/√2)=(6√2+√12)/4=(3√2+2√3)/4

⇒ [ (2√3-√2)/6-(4√3+9√2)9+ (3√2-2√3)/12-(3√2+2√3)/4]=[12√3-6√2-16√3-36√2+9√2-6√3-27√2-18√3]/36=-(28√3-60√2)/36=-4(7√3+15√2)/36= -(7√3+15√2)/9

1 5 1